Impact of Social Media Marketing Towards University Students’ Purchase Intention in the Fashion Industry in Kuala Lumpur - Sheng, Pun Jih; Kaur, Harjinder (Electronic Journal of Business and Management, 2024)
This study examines how social media marketing methods influence customer behaviour, particularly among university students in the fashion business. It emphasises the expanding role of social media platforms in changing purchase intentions and offers practical consequences for marketers and fashion firms looking to effectively target young consumers. It also provides useful information for future research in demographics and industries other than fashion. The study used a survey approach called Google Forms. The respondents were university students based in Kuala Lumpur. The research model was based on the Uses and Gratifications Theory and the Hedonic and Utilitarian Theory, with purchase intention as the dependent variable and social media marketing methods (Facebook, Instagram, YouTube, and user-generated content) as the independent variables. This study examines how social media marketing methods influence customer behaviour, particularly among university students in the fashion business. It emphasises the expanding role of social media platforms in changing purchase intentions and offers practical consequences for marketers and fashion firms looking to effectively target young consumers. It also provides useful information for future research in demographics and industries other than fashion.